Eine neue Art der Gattung Tachinus Gravenhorst aus Nepal (Coleoptera: Staphylinidae). - Schülke, Michael; Kleeberg, Andreas (Contributions to Entomology = Beiträge zur Entomologie, 1997)
Tachinus schmidti sp. n. from Nepal is described as a member of the elongatus-group. Male and female sex characteristics are illustrated. Keywords Coleoptera, Staphylinidae, Tachyporinae, Tachinus, elongatus-group, Nepal, New species. Nomenclatural Acts schmidti Schülke & Kleeberg, 1997 (Tachinus), spec. n.